Կոստանդնուպոլսի հայոց պատրիարք Զավեն Տեր-Եղիայանի գործունեությունն աքսորի տարիներին (1916-1918) - Մանվելյան, Սերգեյ
In 1916, the Young Turks’ government decided to cancel the Armenian Na-tional Constitution of 1863 and suspend the activities of the Armenian Patriarchate of Constantinople. The Patriarch of Constantinople Zaven Ter-Yeghiayan was ex-iled to Baghdad and then to Mosul. He was actively engaged in rescuing Armenian refugees, especially after the occupation of Mosul by the English army. He was supported by the top military echelon and the governor of the city Col. Litchman. After the cease-fire signed on October 30, 1918, Archbishop Zaven Ter-Yeghiayan was also granted amnesty, and with the support of the British Ministry of War went back to Constantinople to regain his patriarchal responsibilities. В 1916 году правительство младотурок приняло решение отменить Армянскую Национальную конституцию 1863 года и приостановить деятельность Армянского Константинопольского Патриархата. Патриарх Завен Тер-Егиаян был сослан в Багдад, а затем в Мосул. Он принимал активное участие в спасении армянских беженцев, особенно после оккупации Мосула англий-ской армией, при поддержке высшего военного командования в лице губернатора города полковника Личмена. После перемирия, подписанного 30 ок-тября 1918 года, архиепископ Завен Тер-Егиаян также был амнистирован и при поддержке британского “Министерства войны” вернулся в Константинополь, чтобы восстановить свои патриаршие обязанности.
Keywords: Հայոց պատրիարքություն; Հայ եկեղեցու գործիչներ